Politics on the homepage, entertainment on social media: news media agenda on their homepages, Facebook and Twitter - Panza Guardatti, Mattía (2019)
This work examines the online agenda of two of the most important newspapers in Argentina -Clarín and La Nación- through quantitative content analysis of the news stories published on their respective homepages and on the official accounts of these two media outlets on Facebook and Twitter. The analysis of 3.780 news shows that newspapers maintain an agenda related to public affairs on their home pages, while on social networks they prioritize news related to non-public topics. The divergence is lowest early in the morning and increases throughout the day. This paper explores the reasons for the differences between the topics selected by the news companies on their homepages and their social media presence.